Thermal design and performance of taper cavity cryomodule for ADS Injector II. (October 2018) - Bai, Feng; Niu, Xiaofei; Wang, Xianjin; Hu, Jianjun; Hu, Yongping; Zhang, Junhui
Highlights: A new type of cryomodule for ADS Injector II is been presented. Unique thermal design and performance of this taper cavity cryomodule are shown in this paper. Some specific design effectively improves the commissioning performance of this cryomodule. Abstract: A β = 0.15 taper cavity cryomodule has been designed for China Accelerator Driven Sub-critical System Injector II (ADS) at the Institute of Modern Physics (IMP) of the Chinese Academy of Science (CAS). And ADS Injector II linac has accelerated 10 mA proton beam to 25 MeV in June of 2017. This cryomodule is the third cryomodule of ADS linac and contains five β = 0.15 taper cavities and five 5.5 T solenoids operating at 4.2 K&1.05 Bar. First cool-down of this cryomodule was completed at the beginning of May in 2017. This paper will report the thermal design and performance of this taper cavity cryomodule.